A comparative analysis of toxicity and treatment outcomes of adaptive radiotherapy and intensity-modulated radiotherapy in cervical cancer - Xiaohan Liu; Wei Tian; Anli Dai; Hui Li; Mei Zhu; Mengsi Zeng; Ronghua Feng; Zhenyu Zhang; Xiaosong Jiang; Yu Wen; Tao Wu; Zemin Xiao (Scientific Reports)
Abstract Adaptive radiotherapy (ART) provides greater benefits than intensity-modulated radiotherapy (IMRT) regarding dosimetric outcomes in patients with cervical cancer. To investigate the clinical benefits of ART, we have collected data from 115 cervical cancer patients who underwent radical radiotherapy at our institution. Fifty-nine patients received a single course of IMRT. Fifty-six patients underwent offline ART, defined as the reduction of the gross tumor volume (GTV) by at least 30% after 30 Gy of radiotherapy, followed by a modified treatment plan for the second-stage. After treatment, 53 patients of ART group achieved a partial response (PR) or completement response (CR), resulting in an objective response rate (ORR) of 94.6% for the ART group, compared to 93.2% for the IMRT group. Patients in both groups exhibited no significant differences in acute toxicities. However, the incidence of chronic constipation was significantly higher in the IMRT group compared to the ART group (p = 0.021). With a median follow-up time of 27 months, the ART group experienced a higher mortality (10/56) than the IMRT group (6/59). However, the difference between the two groups was not statistically significant. In summary, ART may be advantageous in reducing the incidence of chronic constipation among patients with locally advanced cervical cancer, and both clinical prognosis and near-term survival are satisfactory.